Cassava mosaic - Alabi, O.J.; Mulenga, R.; Legg, James P. (CAB International, 2015)
Although cassava shows resilience against a myriad of pests and diseases, including several of viral aetiology, two virus disease complexes, cassava brown streak disease and cassava mosaic disease (CMD), are the major yield-limiting biotic constraints to its production in sub-Sahara Africa. Subsequent studies have recorded the occurrence of many virus species, all of which belong to the genus Begomovirus (family Geminiviridae), in CMD-affected plants. This chapter presents the symptopms, causative viruses, epidemiology, economic impact, monitoring and management of CMD. The genome structure, function and diversity, host range, transmission, detection and distribution of the causal agent are also described. An integrated approach that takes into consideration 'traditional' versus 'novel', 'ancient' versus 'modern', and 'conventional' versus 'unconventional' solutions will hold better promise for a comprehensive ecologically friendly and economically sustainable CMD management effort in sub-Saharan Africa. In line with this, largely neglected components of the CMG-cassava pathosystem such as volunteer cassava plants and alternative hosts of CMGs, abundance of natural enemies of Bemisia tabaci and the use of transgenic resistance will need to form part of an overall CMD management strategy.